The people's peace : civil society organisations and peace processes in the South - Baranyi, Stephen, 1962- (Reports & briefings (Catholic Institute for International Relations), 1998)
This report, based on a CIIR seminar, compares the experiences of civil society organisations in four different peace processes: in Colombia, Guatemala, East Timor and South Africa. It examines how people's organisations have tried to influence the outcome of peace processes in these very different circumstances, and how they have coped with success as well as failure.